Organic materials as smart nanocarriers for drug delivery - Grumezescu, Alexandru Mihai (Oxford, United Kingdom : Elsevier, 2018)
"Organic Materials as Smart Nanocarriers for Drug Delivery presents the latest developments in the area of organic frameworks used in pharmaceutical nanotechnology. An up-to-date overview of organic smart nanocarriers is explored, along with the different types of nanocarriers, including polymeric micelles, cyclodextrins, hydrogels, lipid nanoparticles and nanoemlusions. Written by a diverse range of international academics, this book is a valuable reference for researchers in biomaterials, the pharmaceutical industry, and those who want to learn more about the current applications of organic smart nanocarriers. Explores the most recent molecular- and structure-based applications of organic smart nanocarriers in drug deliveryHighlights different smart nanocarriers and assesses their intricate organic structural properties for improving drug deliveryAssesses how molecular organic frameworks lead to more effective drug delivery systems"--
1. Metal-organic frameworkds as expanding hybrid carriers with diverse therapeutic applications -- 2. Natural and semisynthetic polymers in pharmaceutical nanotechnology -- 3. Current perspectives on drug release studies from polymeric nanoparticles -- 4. Polymeric nanofibers for controlled drug delivery applications -- 5. Polymeric hydrogels for contact lens-based ophthalmic drug delivery systems -- 6. Palm-based nanoemulsions for drug delivery systems -- 7. Strategies for the design and synthesis of pincer-based dendrimers: potential applications -- 8. Nanohydrogels: emerging trend for drug delivery -- 9. Lipid-based nanoparticles for dermal drug delivery -- 10. Lipid-based nanoparticles for cancer diagnosis and therapy -- 11. Lyotropic liquid crystal nanoparticles: a novel improved lipidic drug delivery system -- 12. Vesicular carriers as innovative nanodrug delivery formulations -- 13. Gemini surfactant-based systems for drug and gene delivery -- 14. Self-assembled quaternary ammonium surfactants for pharmaceuticals and biotechnology -- 15 Cyclodextrin-based nanoparticles -- 16. Cyclodextrin nanosponge-based systems in drug delivery and nanotherapeutics: current progress and future prospects.
Off-Campus Access: Athens ID and Password Required
On-Campus Access: No User ID or Password Required
Includes bibliographical references and index.
Mode of access: Internet
Keywords: Drug carriers (Pharmacy).; Drug delivery systems; Nanomedicine; Nanostructured materials; Drug carriers (Pharmacy); Drug delivery systems; MEDICAL -- Pharmacology; Nanomedicine; Nanostructured materials; Drug Delivery Systems; Nanostructures; Drug Carriers; Nanomedicine; Electronic books